"Deepening democracy?" Democratic practices and values in co-operatives operating within a Solidarity Economy framework: a case study of the Tswelelane bakery in Gauteng - Bentes, Saulo de Tarso Vale (My University, 2016)
This research report analyses the relationship between the Solidarity Economy framework and democratic values and practices. The research involved a literature review of the principles informing the Solidarity Economy (SE) framework, the experience of the SE in Brazil compared to South Africa, and the differences compared to conventional co-operatives. The field work involved semi structured interviews and participant observation in a worker co-operative located in Ivory Park, Gauteng. The co-operative is a bakery with approximately seven years of history with struggles and changes. The observation focused on the organization of power relations within the co-operative, the social relations between members themselves, with the community and with another institutions The research found that, despite facing challenges and being a small size cooperative, the social relationships are marked by democratic decision making, a flat, horizontal form of internal organisation and harmonious, collegial social relationships with an overall emphasis on solidarity. It suggests that co-operatives organised in terms of the Solidarity Economy framework have the potential to deepen sustainable democracy. Keywords: Solidarity Economy, Worker Co-operative, South Africa, Brazil, Qualitative method, Leadership, Social Relations, Democracy.
University of the Witwatersrand Faculty of Humanities Department of Sociology/ Global Labour University
Keywords: Solidarity Economy; Worker Co-operative; South Africa; Brazil; Leadership; Social relations; Democracy